2012
DOI: 10.5194/acp-12-5237-2012
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependent halogen activation by N<sub>2</sub>O<sub>5</sub> reactions on halide-doped ice surfaces

Abstract: Abstract. We examined the reaction of N 2 O 5 on frozen halide salt solutions as a function of temperature and composition using a coated wall flow tube technique coupled to a chemical ionization mass spectrometer (CIMS). The molar yield of photo-labile halogen compounds was near unity for almost all conditions studied, with the observed reaction products being nitryl chloride (ClNO 2 ) and/or molecular bromine (Br 2 ). The relative yield of ClNO 2 and Br 2 depended on the ratio of bromide to chloride ions in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
25
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 54 publications
6
25
0
Order By: Relevance
“…2.1.3. CIMS One-second HNO 3 concentrations were quantified by a high-resolution time of flight chemical ionization mass spectrometer (CIMS), which used the I À reagent ion to selectively detect HNO 3 [Slusher et al, 2004;Lopez-Hilfiker et al, 2012;Lee et al, 2014;Lopez-Hilfiker et al, 2016]. In a heated teflon flow tube at low pressure, iodide ions are produced to selectively cluster with HNO 3 in ambient air.…”
Section: Amsmentioning
confidence: 99%
“…2.1.3. CIMS One-second HNO 3 concentrations were quantified by a high-resolution time of flight chemical ionization mass spectrometer (CIMS), which used the I À reagent ion to selectively detect HNO 3 [Slusher et al, 2004;Lopez-Hilfiker et al, 2012;Lee et al, 2014;Lopez-Hilfiker et al, 2016]. In a heated teflon flow tube at low pressure, iodide ions are produced to selectively cluster with HNO 3 in ambient air.…”
Section: Amsmentioning
confidence: 99%
“…Previous studies have reported evidence of a competition between particle-phase chloride and halogens. For example, enhanced Br 2 formation relative to ClNO 2 has been observed on ice at Cl À :Br À ratios <30 (Lopez-Hilfiker et al, 2012). In addition, reaction of N 2 O 5 with dilute NaI and NaBr solutions has shown production of BrNO 2 , Br 2 , and I 2 (e.g., Behnke et al, 1994;Schweitzer et al, 1998).…”
Section: Additional Aqueous Competition Reactionsmentioning
confidence: 99%
“…The output of the 15 N 2 O 5 generation system was verified utilizing two independently-calibrated total nitrogen oxide (NO y ) instruments (National Oceanic and Atmospheric Administration Cavity Ring-down Spectroscopy, NOAA CRDS; Wagner et al, 2011;Wild et al, 2014; and University of California Berkeley thermal dissociation laser-induced fluorescence, TD-LIF; Day et al, 2002;Wooldridge et al, 2010), which agreed to within 1.3%, well within the uncertainties of each technique. The 15 N 2 O 5 was periodically converted to nitryl chloride (Cl 15 NO 2 ) using a wetted salt bed (Kercher et al, 2009;Lopez-Hilfiker et al, 2012). The resulting sample containing Cl 15 NO 2 , H 15 NO 3 , and 15 N 2 O 5 was measured by the HRToF-CIMS and quantified as a sum by the two NO y instruments.…”
Section: Calibration and Artifact Determinationsmentioning
confidence: 99%